COVID-19 Control in Highly Urbanized Philippine Cities: Leveraging Public Health Open-Source Government Data for Epidemic Preparedness and Response - Maria Catherine B. Otero; Lorraine Joy L. Bernolo; Refeim M. Miguel; Zypher Jude G. Regencia; Lyre Anni E. Murao; Emmanuel S. Baja (COVID)
Highly Urbanized Cities (HUCs) in the Philippines were at the forefront of public health surveillance and response during the COVID-19 pandemic. With the rapid spread of COVID-19 to Philippine cities, local government units continuously assessed, adapted, and implemented public health interventions (PHIs) and depended on available open-source government data (OSGD). This study consolidated PHIs in selected HUCs in the Philippines using high-quality OSGD to create a timeline of interventions and document good practices in local COVID-19 control. OSGD resources were collected from February 2020 to January 2023, and the data quality of OSGD was evaluated using the Journal of the American Medical Association (JAMA) benchmarks. A total of 180 metadata sources that met at least two core standards (Authorship and Currency) were included in the analysis. COVID-19 control strategies were analyzed vis-à-vis the rise of COVID-19 cases and types of PHIs, including the control of imported cases, case management, contact management, behavioral modification, and pharmaceutical intervention. Travel bans and hard lockdowns in Luzon early in the pandemic delayed the introduction of COVID-19 to other parts of the country. Good practices of LGUs for local COVID-19 control, such as quarantine passes, curfews and liquor bans, using QR-based contact tracing, massive community testing in high-risk communities, and free public swabbing centers, were implemented to slow down the local spread of COVID-19. With the evolving scenarios in city-level COVID-19 epidemics, local risk assessments based on available OSGD drove the adoption of relevant and innovative control strategies in HUCs in the Philippines. Lessons learned must be integrated into epidemic preparedness and response programs against future emerging or re-emerging infectious diseases.